Association between anti-smoking campaign types and smoking cessation attempts - Dan Bi Kim; Yu Shin Park; Il Yun; Eun-Cheol Park; Sung-In Jang (Elsevier, 2023)
Objective: This study explored the association between anti-smoking campaign types and smoking cessation attempts. Methods: This study included 4,594 individuals (3,292 male and 1,302 female) from the Korea Youth Risk Behavior Web-based Survey (KYRBWS) in 2018 and 2020. The methods of anti-smoking promotion were divided into online, offline, online and offline, and none. Attempts to quit smoking were classified as yes or no. Multiple logistic regression was performed to examine the association between antismoking campaign type and smoking cessation attempts. Results: Those who saw anti-smoking advertisements both online and offline were found to have tried to quit smoking more than those who did not. (Online & offline: male, odds ratio [OR] 1.36; 95% confidence interval [95% CI], 1.08-1.71; female, OR, 1.75; 95% CI 1.21-2.54) In a subgroup analysis of the independent variables into which smoking cessation advertisements were subdivided, males were found to have the highest OR for smoking cessation attempts when they encountered advertisements in newspapers. (Newspaper: male, OR, 2.25; 95% CI, 1.00-5.02) Females had the highest OR for smoking cessation attempts when accessed via the Internet. (Internet: female, OR, 1.93; 95% CI, 1.07-3.50). Conclusion: This study showed that there is a correlation between smoking cessation advertisements and adolescents' smoking cessation attempts. The possibility of smoking cessation attempts is high when encountering smoking cessation advertisements both online and offline. Although offline smoking cessation advertisements have a great effect on adolescents' smoking cessation attempts, it can be confirmed that the frequency of exposure for offline advertisements is less than that for online advertisements.